1990
DOI: 10.2118/16618-pa
|View full text |Cite
|
Sign up to set email alerts
|

Equations for Leak Resistance of API 8-Round Connectors in Tension

Abstract: Summary This paper presents stress and leak-resistance equations based on the theoryof elasticity for API 8-round connectors in tension and compares results ofthese equations to those of the finite-element method (FEM) and full-scalephysical testing. The new equations identify significant nonconservativeaspects inherent in current API methodologies. Introduction Interest concerning leak resistance of API 8-round connectors pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Figure 4 illustrates two proposed criteria to determine if fluid penetration occurs: 1) fluid penetration occurs if fluid pressure exceeds SFCP; 2) fluid penetration occurs if SFCP is zero [13]. Schwind et al [14,15] suggested two parameters to quantify sealability: 1) average pressure on the stab flank and 2) average pressure on stab flank normalized by the internal pressure. Assanelli et al [10] use those criteria to predict sealability, reproducing via FE analysis results of capped-end tests.…”
Section: Review Of Fe Modelling Of Leakage In Casing Connectionsmentioning
confidence: 99%
“…Figure 4 illustrates two proposed criteria to determine if fluid penetration occurs: 1) fluid penetration occurs if fluid pressure exceeds SFCP; 2) fluid penetration occurs if SFCP is zero [13]. Schwind et al [14,15] suggested two parameters to quantify sealability: 1) average pressure on the stab flank and 2) average pressure on stab flank normalized by the internal pressure. Assanelli et al [10] use those criteria to predict sealability, reproducing via FE analysis results of capped-end tests.…”
Section: Review Of Fe Modelling Of Leakage In Casing Connectionsmentioning
confidence: 99%
“…Focusing on the seal failure of threaded connections, several researches have been carried out. Schwind discussed various factors that affect the sealing performance of API round threaded connections, and the equations for stress and leak resistance were proposed based on the elastic theory [9]. Gong studied the effect of the tolerance of thread height, thread angle, and thread taper on the sealing performance of standard API casing threaded connections [10].…”
Section: Introductionmentioning
confidence: 99%
“…Fonte: Adaptado de SCHWIND e WOOLEY (1989). SCHWIND et al (SCHWIND, 1987;SCHWIND et al, 1995) sugerem dois parâmetros para quantificar a estanqueidade:…”
Section: Avaliação Da Estanqueidadeunclassified